2012
DOI: 10.1016/j.fjs.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Scrotal cystic mass as a late presentation of neonatal testicular torsion

Abstract: We present the case of a 1-year-old boy who had had a right scrotal enlargement for 9 months. He experienced a sudden onset of right scrotal enlargement and irritability at 3 months of age. No testis but hydrocele was identified at 5 months by sonography at another hospital. On admission, an elastic mass in the right scrotum measuring 3 cm  2 cm  2 cm was noted. Sonography showed a cystic, thick-walled mass, wherein no testis was identified. Magnetic resonance imaging failed to reveal his right testis along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Similarly, there was a significant volume loss in three of our patients whose pain duration was over 15 h. In a previous study, atrophic testicular tissue was previously shown to have fibrosis on pathological specimens (Antic et al, 2011). A case report with the late admission of acute scrotum showed cystic degeneration after initial necrosis due to testicular torsion (Tan et al, 2012). In the current study, in patients who developed testicular atrophy after torsion, SWE revealed severely increased stiffness in testicular tissue while the part that developed cystic degeneration was softened.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there was a significant volume loss in three of our patients whose pain duration was over 15 h. In a previous study, atrophic testicular tissue was previously shown to have fibrosis on pathological specimens (Antic et al, 2011). A case report with the late admission of acute scrotum showed cystic degeneration after initial necrosis due to testicular torsion (Tan et al, 2012). In the current study, in patients who developed testicular atrophy after torsion, SWE revealed severely increased stiffness in testicular tissue while the part that developed cystic degeneration was softened.…”
Section: Discussionmentioning
confidence: 99%